The Challenge of Indian National Space Policy. Issue 2 (1st September 2016) - Nair, Kiran Krishnan
ABSTRACT: Space capabilities are important for national growth and well-being. They impact civil development and national security in equal measure. At the same time, space capabilities are costly assets with many applications and are in great demand. The need for optimal and balanced exploitation of resources demands a practical space policy that serves to fulfill the demands of most stakeholders and is in line with global trends. In the case of large countries like India, with an equally large population of over 1.28 billion, the complexities are varied and manifold, as are the challenges and opportunities. India's national space policy, at present, is limited in scope with a focus on communication and remote sensing satellites. As India's space capabilities and competencies grow, the need for a broader national space policy rises. India is cognizant of this, and this article discusses the various challenges in the formulation of a comprehensive national space policy for India.